Group flow: A scoping review of definitions, theoretical approaches, measures and findings. - Fabian Pels; Jens Kleinert; Florian Mennigen (PLoS ONE)
The purpose of this article is to provide a scoping review of the current literature on group flow. Based on the PRISMA-guidelines for systematic reviews, 26 publications were identified that met the inclusion criteria. Publication analyses comprised an individual consideration of each publication and a systematic, integrative synthesis of all publications. Analyses identified heterogeneous group flow definitions across publications, supporting the need for an integrative definition. Further heterogeneity existed in the theoretical approaches and measures used, highlighting the need for a comprehensive theory and a measurement standard. Components (e.g., synchronization), antecedents (e.g., trust), and outcomes (e.g., well-being) of group flow were identified in publications that presented empirical studies, some of which that showed similarities between characteristics of group flow and individual flow and others that showed aspects unique to group flow. Overall, this scoping review reveals the need for a systematic research program on group flow.